The use of knowledge management by innovators: empirical evidence for Germany - Uwe Cantner; Kristin Joel; Tobias Schmidt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In this paper we investigate factors that influence a firms decision to implement knowledge management practices. Our focus is on knowledge management practices implemented to increase collaboration between actors within a firm on innovation activities. Using information on over 1,500 innovative German firms from the Mannheim Innovationpanel of 2003, we find that an innovation strategy targeted at consumers and continuous R&D activities is positively related to KM usage. In addition, more general firm characteristics like size and the industry of a firm do influence the decision to use knowledge management as well.
Keywords: D23; O31; O32; 330; knowledge management; innovation; Mannheim Innovationpanel; Wissensmanagement; Wissenstransfer; Innovation; Industrielle Forschung; Deutschland